Impacts of inundation on bird assemblages in forests in and around a Hydrodam in Terengganu, Malaysia - Farah Shafawati Mohd-Taib; Siti Nabilah Ishak; Mohammad Saiful Mansor; Shukor Md-Nor (Penerbit Universiti Kebangsaan Malaysia, 2018)
Despite the increasing numbers of hydrodam worldwide, only a handful of studies evaluated their impacts on biodiversity. Compared to terrestrial animals, birds were thought to be less affected by inundation process, following impoundment. At the Hulu Terengganu Hydroelectric Dam in Peninsular Malaysia, our study compared species assemblages and diversity of birds within the dam area (i.e. the dam reservoir and catchment area) after recent logging and inundation in relation to a nearby forest logged 30 years ago. Using point count and mist-netting techniques, we recorded a total of 64 species (Shannon Index (H’) = 3.827) in the dam area and 91 species (H’=3.99) in historically-logged forests. Insectivore species richness was significantly higher in the historically-logged forests (Mann-Whitney: Z=4.339, N=205, p<0.005). These results indicated that richness and diversity of bird species assemblages appear to decline following recent inundation phase. Nevertheless, the forests in the dam area still harbour charismatic species such as eagles (Family: Accipitridae) and hornbills (Family: Bucerotidae) which suggests that this habitat is relatively important for birds.